Green composites based on polypropylene matrix and hydrophobized spend coffee ground (SCG) powder. (1st September 2015) - García-García, D.; Carbonell, A.; Samper, M.D.; García-Sanoguera, D.; Balart, R.
Abstract: Green composites were prepared with polypropylene matrix and 20 wt.% spent coffee ground (SCG) powder for uses as a wood plastic composite (WPC). The effects of hydrophobic treatment with palmitoyl chloride on SCG powder is compared with conventional surface treatment based on silanization with (3-glycidyloxypropyl) trimethoxysilane and the use of a maleated copolymer compatibilizer (polypropylene-graft-maleic anhydride, PP- g -MA) in terms of mechanical properties, morphology, thermal properties and water uptake. Composites were previously mixed in a twin-screw co-rotating extruder and subsequently subjected to injection moulding. The comparative effect of the different surface treatments and or compatibilizers on mechanical performance was studied by flexural, impact tests and dynamic mechanical thermal analysis (DMTA-torsion); in addition, the stabilizing effect of SCG was revealed by differential scanning calorimetry (DSC) and thermogravymetric analysis (TGA). As one of the main drawbacks of wood plastic composites and natural fibre reinforced plastics is the moisture gain, water uptake tests were carried out in order to quantify the effectiveness of the hydrophobization process with palmitoyl chloride. Results show a slight increase in flexural modulus for composites with both untreated and treated/compatibilized SCG powder (20 wt.%). As expected, thermal stability is improved as indicated by an increase of more than 8% in the onset degradation temperature by DSC if compared to unfilled polypropylene. Fracture analysis by scanning electron microscopy (SEM) shows better particle dispersion for PP-SCG composites with hydrophobized SCG with palmitoyl chloride treatment; in addition a remarkable decrease in water uptake is observed for composites with hydrophobized SCG.